2011
DOI: 10.1111/j.1365-294x.2010.04974.x
|View full text |Cite
|
Sign up to set email alerts
|

How do insects react to novel inherited symbionts? A microarray analysis of Drosophila melanogaster response to the presence of natural and introduced Spiroplasma

Abstract: Maternally inherited endosymbionts are found in numerous insect species and have various effects on host ecology. New symbioses are most commonly established following lateral transfer of an existing symbiont from one host species to another. Laboratory study has demonstrated that symbionts commonly perform poorly in novel hosts, with weak vertical transmission and maladaptive pathogenicity being observed in the generations following transfer. This poor performance probably limits symbiont occurrence. We here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…It is also worth noting that a recent microarray study of D . melanogaster harboring different strains of Spiroplasma revealed that these had the capacity to perturb the expression of host yolk genes (40). This suggests that that the interaction between Spiroplasma and yolk might be multifaceted, but the implications of these gene expression changes for Spiroplasma transmission are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that a recent microarray study of D . melanogaster harboring different strains of Spiroplasma revealed that these had the capacity to perturb the expression of host yolk genes (40). This suggests that that the interaction between Spiroplasma and yolk might be multifaceted, but the implications of these gene expression changes for Spiroplasma transmission are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Spiroplasma typically occur extracellularly in the host hemolymph while Wolbachia are predominately intracellular, and Spiroplasma cause little apparent immune activation in their hosts [30],[31]. Spiroplasma may be more susceptible to immune effectors active in the host hemolymph due to their extracellular lifestyle, and thus under selection to avoid or even suppress host immune activation (e.g., [30]). Mechanisms other than host immune priming might therefore account for Spiroplasma -mediated defense.…”
Section: Spiroplasma: Under the Radarmentioning
confidence: 99%
“…The literature on possible mechanisms is fragmentary and contradictory. Spiroplasma in D. melanogaster is known to evade systemic immune attack (Hurst, Anbutsu, Kutsukake, & Fukatsu, ; Hutchence, Fischer, Paterson, & Hurst, ) and to compete with the host for key nutrients, specifically lipids (Herren et al, ), raising the possibility that Wolbachia in D. neotestacea may promote Spiroplasma populations by attenuating the systemic immune system or enhancing lipid availability in the haemolymph. However, these inferences fit poorly with other data sets that point to Wolbachia ‐mediated promotion of host immune responsiveness (Gupta et al, ) and depletion of nutrients, notably sterols (Caragata et al, ) which are required by Spiroplasma .…”
Section: Discussionmentioning
confidence: 99%